Polynomial Olympiads Questions

Download as pdf or txt
Download as pdf or txt
You are on page 1of 3

WORKSHEET

CHAPTER 5: POLYNOMIALS AND SQUARE


ROOTS OF ALGEBRAIC EXPRESSIONS

Directions for questions from 1 to 5: Select the correct 9. The remainder obtained when x4 + 3x2 - 2x - 10 is
alternative from the given options. divided by x + 2 is _________.
1. Find the square root of 10. Solve for (2x + 3y)2 + (2x - 3y)2.
16x 4 − 96x 3 + 216x 2 − 216x + 81.
Directions for questions from 11 to 15: Answer the
(a) 4x2 - 12x + 9 (b) 4x2 + 12x - 9 following questions.
(c) 2x2 - 6x + 9 (d) 2x2 - 2x + 3 11. The following steps are involved in showing that if a
2. If ax4 + bx3y + cx2y2 + dxy3 + ey4 is a complete homog- + b + c = 0, then a3 + b3 + c3 = 3abc. Arrange them in
enous and symmetric expression of degree 4 in two sequential order.
variables x and y, then which of the following neces- (A) a3 + b3 + 3ab(-c) = -c3
sarily be true? (B) (a + b)3 = (-c)3
(a) a = e (b) a = b = c = d = e (C) a + b + c = 0 ⇒ a + b = - c
(c) b = d (d) Both (a) and (c) (D) a3 + b3 + 3ab(a + b) = -c3
3. Which of the following is a factor of x4 + x2 + 1? (E) a3 + b3 + c3 = 3abc
(a) x2 + x - 1 (b) x2 - x - 1 12. Find the square root of (3x + 3y + xy)2 - 12xy (x + 3).
(c) x2 - x + 1 (d) -x2 - x - 1
13. Find the HCF of the polynomials f(x) = (x - 1)2
4. If the LCM of two polynomials f(x) and g(x) is - 4)
(x2 (x2 - 1)2 (x + 2)2 and g(x) = (x2 - 2x + 1) (x + 2)3
(x + 3), then what can be the HCF of f(x) and g(x)? (x + 1)3.
(a) x2 + 5x + 6 (b) x2 + x - 6 14. Solve for
(c) x + 5x - 6
( x 2 + 7x + 12 ) ( x 2 + 8x + 15) ( x 2 + 9x + 20 ) .
2 (d) None of these
5. If (x + 1) (x + 3) (x + 5) (x + 7) + p is a perfect square,
then p = _________. 15. Match the values of Column A with those of
(a) 16 (b) 39 Column B.
(c) 64 (d) 36 Column A Column B
(i) (3x - 2y)2 (a) Homogeneous
Directions for questions from 6 to 10: Evaluate the
following. (ii) (x + y + z)2 (b) Symmetric
6. Factorize: 4x4 + 16. (iii) 3x2 - 2xy + 5x (c) Homogeneous and
+ 5y + 3y2 cyclic
7. If the LCM of two polynomials f(x) and g(x) is (x - 1)
(x - 2)2 (x - 3)3, then f(x)·g(x) can be _________. (iv) 3x3 - 3y2 - 3x (d) Non-homogenous
+ 3y and non-symmetric
8. What will be the value of k + l, if x4 - 14x3 + 71x2 +
kx + l is a perfect square?

D.1

M05 IIT Foundation Maths Grade 9_DW.indd 1 14-Feb-22 11:08:14 AM


ANSWER KEYS
1. (a) 2. (d) 3. (c) 4. (d) 5. (a)
6. 4(x2 + 2x + 2) (x2 - 2x + 2) 7. (x - 1) (x - 2)2 (x - 3)3 8. -33
9. 22 10. 8x + 18y
2 2 11. CBDAE 12. 3x - 3y - xy
13. (x - 1)2 (x + 1)2 (x + 2)2 14. (x + 3) (x + 4) (x + 5)
15. (i) → (a); (ii) → (c); (iii) → (b); (iv) → (d)

Hints and Explanation


1. 4x2 - 12x + 9 6. 4x4 + 16 = (2x2)2 + 42
4x2 16x4 - 96x3 + 216x2-216x + 81 = (2x2)2 + 2(2x2) 4 + 42 - 2(2x2) 4
16x4 = (2x2)2 + 16x2+ 42 - 16x2
= (2x2 + 4)2- (4x)2
8x2 - 12x -96x3 + 216x2-216x + 81
= (2x2 + 4x + 4) (2x2 - 4x + 4)
-12x -96x3 + 144x2
= 4(x2 + 2x + 2) (x2 - 2x + 2)
8x2 - 24x + 9 72x2 - 216x + 81
7. f(x) × g(x) = HCF × LCM
72x2 - 216x + 81
When HCF = 1, f(x) × g(x) = LCM.
-  +   -
8. x4 - 14x3 + 71x2 + kx + l is a perfect square.
0
x2 - 7x + 11
\ Square root of the given expression is 4x2 - 12x + 9. x2 x4 - 14x3 + 71x2 + kx + l
Hence, the correct option is (a). x4
2. G
 iven expression is a complete homogenous and sym- 2x2 - 7x -14x3 + 71x2 + kx +l
metric expression in two variables x and y. - 7x -14x3 + 49x2
\ a = e and b = d +  -
Hence, the correct option is (d). 2x2 - 14x 22x2 + kx + l
3. x4 +
+1= x2 + - (x2 1)2 x2 + 11 22x2 - 154x + 121
= (x + x + 1) (x2 - x + 1)
2
-   +   -
Hence, the correct option is (c). 0
 he HCF of f(x) and g(x) is a factor of the LCM of f(x)
4. T ⇒ k = - 154 and l = 121
and g(x). k + l = -154 + 121= -33
\ Option (d) follows.  et f(x) = x4 + 3x2 - 2x - 10 and divisor = x + 2
9. L
Hence, the correct option is (d). Remainder = f(-2)
5. (x + 1) (x + 3) (x + 5) (x + 7) + p = (-2)4 + 3(-2)2 - 2 (-2) - 10
= (x2 + 8x + 7) (x2 + 8x + 15) + p = 16 + 12 + 4 - 10
= (a + 7) (a + 15) + p (Let us assume that x2 + 8x = a.) = 22
= a2 + 22a + 105 + p  e know that (a + b)2 + (a - b)2 = 2a2 + 2b2
10. W
= a2 + 2 (a) (11) + (105 + p) is perfect square. \ (2x + 3y)2 + (2x - 3y)2
⇒ 105 + p = 112 = 2(2x)2 + 2(3y)2
p = 16 = 8x2 + 18y2
Hence, the correct option is (a).

D.2

M05 IIT Foundation Maths Grade 9_DW.indd 2 14-Feb-22 11:08:15 AM


11. CBDAE is the required sequential order. x2 + 9x + 20 = (x + 4) (x + 5)
12. (3x + 3y + xy)2 -12xy (x + 3) ( x 2 + 7x + 12 ) ( x 2 + 8x + 15) ( x 2 + 9x + 20 )
= (3x + 3y + xy)2 -4(3x) (y) (x + 3)
= ( x + 3)2 ( x + 4 )2 ( x + 5)2
= (3x + 3y + xy)2 -4(3x) (xy + 3y)
= (x + 3) (x + 4) (x + 5)
= [3x - (3y + xy)]2 ∵(A + B)2 - 4AB = (A - B) + 2
= (3x - 3y - xy)2 15. (i) → (a); (3x - 2y)2 = 9x2 -12xy + 4y2 is a homoge-
\Square root of the given expression is 3x - 3y - xy neous expression.

13. f(x) = (x - 1)2 (x2 - 1) 2(x + 2)2 (ii) → (c); (x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz +
= (x - 1)4 (x + 1)2 (x + 2)2 2zx is a homogeneous cyclic expression.
g(x) = (x2 - 2x + 1) (x + 2)3 (x + 1)3 (iii) → (b); 3x2 - 2xy + 5x + 5y + 3y2 is a symmetric

= (x - 1)2 (x + 2)3 (x + 1)3 expression.
\ HCF = (x - 1)2 (x + 2)2 (x + 1)2 (iv) → (d); 3x3 - 3y2 - 3x + 3y is a non-homogeneous
14. x 2 + 7x + 12 = (x + 3) (x + 4) and non-symmetric expression.
x2 + 8x + 15 = (x + 3) (x + 5)

D.3

M05 IIT Foundation Maths Grade 9_DW.indd 3 14-Feb-22 11:08:16 AM

You might also like